Impact of Saccharomyces cerevisiae strains on traditional sparkling wines production. (July 2018) - Di Gianvito, Paola; Perpetuini, Giorgia; Tittarelli, Fabrizia; Schirone, Maria; Arfelli, Giuseppe; Piva, Andrea; Patrignani, Francesca; Lanciotti, Rosalba; Olivastri, Lino; Suzzi, Giovanna; Tofalo, Rosanna
Abstract: Sparkling wine fermentation is a challenge for yeasts due to the hostile conditions. A phenotype sought in starters is flocculation, because it reduces riddling time. For this reason, six flocculent Saccharomyces cerevisiae wine strains with different flocculation degree and autolytic activity and two commercial strains were tested for traditional sparkling wine production in a winery. Yeast viability, free aminoacids and high molecular weight nitrogen release and physico-chemical composition of sparkling wines were evaluated. Moreover, strains were tested for their aromatic potential. Obtained data revealed that flocculent yeasts presented oenological performances (in terms of fermentation rate, maximum pressure reached, free aminoacids - AAN and high molecular weight nitrogen - HMWN release) similar to the commercial strains. All considered strains were able to complete fermentation and viable cells of all strains were detected in all sparkling wines produced even after 6 months. F6789 and F10471 strains showed slow fermentation kinetics reaching the maximum of pressure at 180 days. Regarding nitrogen compounds release, FI strain was characterized by the highest amount of AAN and HMWN released, followed by F6789. Strains showed a considerable diversification in terms of number and amount of aroma molecules produced and sparkling wines obtained with autochthonous flocculent strains presented a higher amount of alcohols and esters already after 3 months. Further studies are necessary to select starter strains to improve traditional sparkling wines production. Graphical abstract: Highlights: Six flocculent S. cerevisiae for sparkling wine production were studied. Flocculent S. cerevisiae strains produced wine with different oenological characteristics. High esters production was related with high autolytic activity.